Teens Talk Vaping: A co-produced participatory study exploring teens' reflections on vaping experiences and exposures in their everyday environments - Stephanie E. Coen; Kendra Nelson Ferguson; Shauna M. Burke; Timothy-Jireh E. Dela Cruz; Laila Girum; Gabriela I. Guisandes Bueno; Rebecca Haines-Saah; Tanya Iwas; Bhargav Kandlakuti; Aliana Manji; Purushoth Megarajah; Ricardo Soto Canales; et al. (Elsevier, 2023)
Abstract: Increasing prevalence of vaping (e-cigarette use) among youth in Canada and elsewhere has become a serious public health concern. The Teens Talk Vaping project sought to co-produce research about teen vaping with teens to generate in-depth qualitative evidence about the everyday socio-environmental dimensions of teen vaping experiences and exposures across perspectives of both teens who vape and those who do not. Our participatory approach included a capacity-building programme to train teen team members to contribute to the project as 'co-researchers', equipping them with the research skills necessary to contribute to all phases of the project, from data collection through to knowledge translation. Paired with adult researchers, teen co-researchers facilitated 7 online focus groups with teens (n=17) from across Canada, including teens who vaped (n=3) and those who did not (n=14). Our participatory thematic analysis generated five themes: (1) Secrecy and surveillance at school; (2) Online omnipresence; (3) Social pressures and positionings; (4) (Un)restricted mobilities and access; and (5) Re-thinking school-based vaping education. Our findings reveal the extent to which exposure to vaping is deeply embedded and normalized in the everyday micro-geographies of teens in Canada as seemingly 'everywhere.' Teen vaping prevention efforts must be equity-centred, youth-driven, and take account of the nuanced ways in which vaping is layered into the day-to-day online and offline contexts of young people's lives.